KOMPILASI HUKUM ISLAM: KONSEP PERSETUJUAN WANITA DALAM PERNIKAHAN PANDANGAN IBN QAYYIM AL-JAWZIYAH DAN KOMPILASI HUKUM ISLA - superadmin superadmin (Al Naqdu, 2020)
Marriage is a high respect and appreciation given to humans from Allah SWTamong other creatures. In the Compilation of Islamic Law, Chapter II article 2 states:"Marriage is a very strong contract (mitsaqan galiza) to carry out the commands ofAllah and His Apostles and is a worship for those who carry it out. Marriage has theaim to realize a concept of sakinah, mawaddah and warahmah. Therefore, it needscareful consideration and can fulfill the purpose of marriage, among the things that canachieve the goal of marriage is the consent or freedom of a woman in determining herfuture husband.The results of this study, Ibn Qayyim al-Jawziyyah who is one of the greatfigures in the Islamic world with his work Zaadul Ma'ad, he believes the approval ofwomen in marriage is a mandatory, while the priests of the madhabs declare it is asunnah, all of which have a foundation of argumentation that can be accounted for.Indonesian people as followers of the Syafi'i madhab, which states that the consent ofgirls in marriage is sunnah, without any agreement marriage is still valid, but in reality,marriage law and Islamic law compilation are in line with the concept of Ibn Qoyyimal-Jawziyyah which requires the approval of women with the specified age